Integration of the athena vortex lattice aerodynamic analysis software into the multivariate design synthesis of a blended wing body aircraft - Okonkwo, Paul; Jemitola, Paul (Heliyon, 2023)
This paper describes the process of integrating the Athena Vortex Lattice aerodynamics solver into a conceptual design environment for the multivariate design synthesis and optimisation of a Blended Wing Body (BWB) Aircraft. The work is derived from a PhD study, by one of the authors, which developed a design methodology for the conceptual design synthesis, analysis and optimisation of a BWB aircraft. This research was driven by the desire to utilise proven aerodynamic solvers, written in legacy codes, in modern computational design environments in order to improve the accuracy and fidelity in the design of novel aircraft configurations. The Athena Vortex Lattice code is a legacy code written in the FORTRAN programming language and developed at the Massachusetts Institute of Technology by Mark Drela while the multivariate conceptual design synthesis and optimisation was implemented in JAVA object oriented programming tool. The result from this study is the successful integration of the AVL software into the JAVA programming environment for the multivariate design synthesis optimisation of the BWB without loss of accuracy. The successful integration of these codes permit a more accurate design synthesis, analysis and optimisation of the novel aircraft configuration in the absence of a tailor-made and realistic empirical aerodynamic analysis model for the BWB Aircraft. Additionally, this research enables the automation of the design process and the accomplishment of the multivariate optimisation.